2014
DOI: 10.1016/j.niox.2014.04.008
|View full text |Cite
|
Sign up to set email alerts
|

AP39, a novel mitochondria-targeted hydrogen sulfide donor, stimulates cellular bioenergetics, exerts cytoprotective effects and protects against the loss of mitochondrial DNA integrity in oxidatively stressed endothelial cells in vitro

Abstract: The purpose of the current study was to investigate the effect of the recently synthesized mitochondrially-targeted H2S donor, AP39 [10-oxo-10-(4-(3-thioxo-3H-1,2-dithiol-5yl)phenoxy)decyl) triphenylphosphonium bromide], on bioenergetics, viability, and mitochondrial DNA integrity in bEnd.3 murine microvascular endothelial cells in vitro, under normal conditions, and during oxidative stress. Intracellular H2S was assessed by the fluorescent dye 7-azido-4-methylcoumarin. For the measurement of bioenergetic func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
207
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 246 publications
(232 citation statements)
references
References 83 publications
15
207
0
10
Order By: Relevance
“…Cells were loaded with 10 μmol/L of the fluorescent H 2 S probe 7-azido-4-methylcoumarin (AzMC) for 30 min as described (40). 3-MP was added at various concentrations and cells were further incubated for 1 h. Cells were washed three times with phosphatebuffered saline (PBS), and the specific fluorescence of the dye was visualized using Nikon Eclipse 80i inverted microscope and NIS-Elements software.…”
Section: Measurement Of H 2 S Production Bend3 Cells (Live Cells and mentioning
confidence: 99%
See 2 more Smart Citations
“…Cells were loaded with 10 μmol/L of the fluorescent H 2 S probe 7-azido-4-methylcoumarin (AzMC) for 30 min as described (40). 3-MP was added at various concentrations and cells were further incubated for 1 h. Cells were washed three times with phosphatebuffered saline (PBS), and the specific fluorescence of the dye was visualized using Nikon Eclipse 80i inverted microscope and NIS-Elements software.…”
Section: Measurement Of H 2 S Production Bend3 Cells (Live Cells and mentioning
confidence: 99%
“…Whole blood was collected 30 min later in K 2 EDTA blood collection tubes and centrifuged at 4°C for 15 min at 2000g. Plasma was isolated and H 2 S levels were measured with the fluorescent H 2 S probe 7-azido-4-methylcoumarin (AzMC) (40). After incubation of 200 μL of plasma with 10 μmol/L AzMC, the fluorescence was measured using SpectraMax M2 microplate reader (Molecular Devices, Sunnyvale, CA, USA.)…”
Section: Plasma H 2 S Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…AP39, a sulfide donor with a mitochondria-targeting moiety, has been shown to increase intracellular H 2 S in these organelles as detected by the H 2 S probe 7-azido-4-methylcoumarin. It was also shown that AP39, at 100 nM, was able to prevent glucose oxidase-induced mitochondrial oxidative stress (113). Table 1 …”
Section: ϫmentioning
confidence: 99%
“…In the case of NO or H 2 S, precursors stimulating endogenous release of the gas can be administered or enzymatic synthesis of the compounds can be induced (Szczesny et al, 2014;Gero et al, 2016). However, with CH 4 , direct delivery is the only feasible option.…”
Section: The Kinetics Of Ch 4 Transport In Vivomentioning
confidence: 99%